125k views
0 votes
If P(x) = -2x2 + 3x – 5 and Q(x) = 5x – 2, form a simplified expression for P(x) - Q(x).

User Whymath
by
4.6k points

1 Answer

2 votes

Answer:


-2x^2-2x-3

Step-by-step explanation:

Given the functions P(x) and Q(x) defined as follows:


\begin{gathered} P\mleft(x\mright)=-2x^2+3x-5 \\ Q\mleft(x\mright)=5x-2 \end{gathered}

Then:


\begin{gathered} P(x)-Q(x)=(-2x^2+3x-5)-(5x-2) \\ =-2x^2+3x-5-5x+2 \\ =-2x^2-2x-3 \end{gathered}

A simplified expression for P(x)-Q(x) is:


-2x^2-2x-3

User Sinthya
by
4.6k points